Laughing at Numbers: Evidence for Numeracy in the “Philogelos” - Brodersen , Kai (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2020)
Ancient numeracy is reasonably well attested in scientific sources. However, any study of applied mathematics faces the problem of a dearth of evidence. The paper suggests that the jokes collected in the “Philogelos” provide such evidence, and discusses the failings which are referred to in these jokes.